Assessment of pharmacokinetics, safety, and tolerability following twice‐daily administration of molnupiravir for 10 days in healthy participants - Marian Iwamoto; Kelly E. Duncan; Prachi K. Wickremasingha; Tian Zhao; Maria V. Liberti; Lieselotte Lemoine; Tatjana Decaesteker; Sylvie Rottey; Brian M. Maas; Gillian Gillespie; S. Aubrey Stoch (Wiley, 2023)
Abstract Molnupiravir is an orally administered, small‐molecule ribonucleoside prodrug of β‐D‐N4‐hydroxycytidine (NHC) that has demonstrated potent, broad‐spectrum preclinical activity against RNA viruses and has a high barrier to the development of resistance. A double‐blind, placebo‐controlled, phase I trial was conducted to evaluate the pharmacokinetics (PKs), safety, and tolerability of 10.5‐day administration of multiple doses of molnupiravir and its metabolites in healthy, adult participants. Participants were randomly assigned (3:1) to receive molnupiravir (400 mg [n = 6], 600 mg [n = 6], and 800 mg [n = 12]) or matching placebo (n = 8) every 12 h (q12h) for 10.5 days. Blood was collected to evaluate the PKs of NHC in plasma and of its active metabolite, NHC‐triphosphate (NHC‐TP), in peripheral blood mononuclear cells (PBMCs). Molnupiravir was generally well‐tolerated. All adverse events were mild or moderate in severity and none led to treatment discontinuation. No clinically meaningful dose‐related safety findings were observed. Mean time to maximal concentration was ~1.50 to 1.98 h for plasma NHC and ~4.00 to 8.06 h for PBMC NHC‐TP. Accumulation was minimal (<1.2) for NHC and ~2‐ to 2.5‐fold for NHC‐TP. Plasma NHC PKs was generally dose proportional, and PBMC NHC‐TP PKs was less than dose proportional over the dose range studied. NHC and NHC‐TP PK support twice‐daily administration. Overall, molnupiravir administered at up to 800 mg q12h for 10.5 days was generally well‐tolerated in healthy participants with dose‐linear PKs, supporting the evaluation of longer molnupiravir dosing up to 10 days in future clinical trials.